RANCANG BANGUN MEDIA PEMBELAJARAN INTERAKTIF KOMPUTER DAN JARINGAN DASAR KELAS X SMK - Ichwan Chani; Nurindah Dwiyani (Universitas Negeri Padang, 2019)
This research discusses discussesthe advantage of information technology as a learning aid that is by by designing interactive multimedia learning on basic computer and networking at class X in vocational school. The research aims to design a valid and practical interactive CD learning media using Adobe Director 11.5 software and supported by other media applications. In designing the material the researcher uses the classic tutorial method. The instruments carried out by researchers to collect data were by filling out questionnaires on the validity of the media carried out by 2 media lecturers (experts) who included aspects of media content, presentation and format as well as practical assessment of media carried out by 2 subject teachers and 5 students. Based on the results of the assessment has been conducted on the validity of the media, the results obtained with an average value of 0.79 and the value of practicality of the media obtained an average yield of 84.38% and 83%. So that it can be concluded that the interactive CD learning media designed using the adobe director 11.5 application is feasible and practical to use in Computer lessons and Class X Basic Networks in vocational school Keywords: Instructional Media, Adobe Director 11.5, Basic Computer And Network.